PENGARUH JUMLAH WAJIB PAJAK BADAN, SURAT SETORAN PAJAK YANG DITERIMA DAN KEPATUHAN WAJIB PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN PASAL 25 (STUDI PADA KKP PRATAMA CANDISARI SEMARANG TAHUN 2010 â 2013) - Mita Rachmawati, 10.05.52.0048; Nurhayati, Ida (Students Journal of Accounting and Banking, 2014)
Tax plays a very important in the implementation of development in Indonesia, various programs have been applied to the community to provide education / understanding of taxation continues to run and continuously performed each year. Income Tax has the criteria as a revenue source and continuous elastic. Therefore, it should gradually become an efficient instrument for increasing state revenue. This study aims to determine whether there is influence taxpayer number, SSP received and Compliance Obligation towards the acceptance rate of income tax article 25. This study uses secondary data obtained from the Tax Office (KPP) Primary Candisari Semarang. Data analysis method used is the classical assumption and subsequent hypothesis testing. The statistical method used is multiple linear regression analysis. The results of research conducted can be seen that the amount of taxpayer partially significant effect on income tax revenue received by the SSP article 25. partially insignificant effect to article 25 of income tax revenue and tax compliance insignificant effect on income tax receipts article 25. simultaneously research results Number of Taxpayers, SSP received significant effect on the acceptance rate of income tax article 25 amounting to 58, 6%, while the remaining 41.4% is influenced by other factors not described in this studyKeywords: Number of Taxpayers, SSP, Taxpayer Compliance, and income tax revenue 25